Reflecting on Training to Facilitate Collaborative Online International Learning Courses - Amy M. Anderson (Journal of Scholarly Engagement)
The purpose of this reflective practice was to explore an unexpected revelation that Collaborative Online International Learning (COIL) courses are an engaging and equitable way to enhance my students’ intercultural communication skills. This discovery happened after participating in a COIL training designed to mimic a virtual global exchange course. In this training, I learned to work collaboratively with an international teaching partner to design a course that would include a problem-based learning project with students from the United States and Brazil. Through the reflective process, my views about online learning were transformed, and I discovered that virtual learning could be collaborative and engaging. I also realized that COIL is a cost-effective alternative to study abroad programs where students can learn about various cultures. This reflective manuscript details my experience as I participated in training to facilitate COIL courses. A subsequent manuscript will elaborate on the reflective practice of my experience teaching a COIL class.